Being and Event Introduction to the Philosophy of Alain Badiou - Badleh, Jala (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
Being and Event is the title of the most prominent book of the French philosopher Alain Badiou, but it’s also a title of an entire philosophical space. Between the two sides of this title, the philosophy has reorganized all the traditional philosophical concepts, especially the truth and the subject. In this context, Badiou’s philosophy is particularly affluent, because it returned back to the very beginning of the philosophy, and launched a discussion with the most eminent philosophical moments in the history of philosophy. In this article, we represent the outlines of this philosopher’s doctrine, it’s the first representation of its kind in Arabic, and we discuss the most important topics he put up, especially the political ones.